Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.virusres.2008.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A natural tetranortriterpenoid with immunomodulating properties as a potential anti-HSV agent

Abstract: Meliacine (MA), an antiviral principle present in partially purified leaf extracts of Melia azedarach L., prevents the development of herpetic stromal keratitis (HSK) in mice by diminishing the viral load in the eye and the severity of lesions caused by a virus-induced immunopathological reaction. The tetranortriterpenoid 1-cinnamoyl-3,11-dihydroxymeliacarpin (CDM), obtained from MA purification, displays anti-herpetic activity and impedes nuclear factor kappaB (NF-kappaB) activation in HSV-1 infected conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 33 publications
(48 reference statements)
1
32
0
1
Order By: Relevance
“…We found that CDM delays the transport of viral glycoproteins that would account for the strong inhibition on viral multiplication (Barquero et al, 2004;Bueno et al, 2010). CDM also decreases IL-6 production in HSV-1-infected corneal cells, enhances TNF-α and reduces IL-6 secretion when macrophages are either infected with HSV-1 or stimulated with LPS (Bueno et al, 2009).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We found that CDM delays the transport of viral glycoproteins that would account for the strong inhibition on viral multiplication (Barquero et al, 2004;Bueno et al, 2010). CDM also decreases IL-6 production in HSV-1-infected corneal cells, enhances TNF-α and reduces IL-6 secretion when macrophages are either infected with HSV-1 or stimulated with LPS (Bueno et al, 2009).…”
Section: Introductionmentioning
confidence: 72%
“…Considering that CDM suppressed IL-6 production in J774A.1 and HCLE cells infected with HSV-1 and stimulated with LPS (Bueno et al, 2009), and that IL-6 can stimulate corneal cells and macrophages to secrete VEGF (Biswas et al, 2006;M.E. Zheng et al, 2001), we decided to investigate the effect of CDM on VEGF transcription.…”
Section: Effect Of Cdm On Vegf Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Alpha glucosidase (2U/ml) was premixed with 20 µl of azadirachtolide at various concentrations (10,20,40,60, 80 and 100 µg/ml) and incubated for 5 min at 37ºC. 1mM para-nitrophenyl glucopyanoside (20 µl) in 50mM of phosphate buffer (pH 6.8) was added to initiate the reaction.…”
Section: In Vitro Alpha Glucosidase Inhibitory Assaymentioning
confidence: 99%
“…[8] Tetranortriterpenoids has been reported for anticancer, antiviral, anti-allergic and anti-inflammatory activities. [9][10][11][12] There is no report on azadirachtolide (tetranortriterpenoid from Azadirachta indica leaves) for antidiabetic and hypolipidemic activities. Therefore, the effect of azadirachtolide (tetranortriterpenoid from Azadirachta indica leaves) on blood glucose and serum lipid profiles on streptozotocin-induced diabetic rats was investigated.…”
Section: Introductionmentioning
confidence: 99%